Resettlement and citizenship in Iceland: The role and position of halfway house Vernd - Pakes, Francis (International journal of law, crime and justice, 2025)
Halfway houses exist to serve as a bridge between prison and society, to enable prisoners to experience a softer landing back into society. Halfway houses are typically small urban or suburban institutions where between 10 and 30 residents live whilst they work, learn or engage in other activities. They are common in the Nordic countries yet for the most part have largely escaped criminological scrutiny. This article focuses on Iceland’s only halfway house, called Vernd after the charity that founded it. Despite being outside the prison system it occupies a prominent place in the penal journey of about half of all prisoners. We consider official data on turnover, and bring in voices and opinions from residents to examine to what extent this halfway house embodies pervasive punishment, and in doing so it considers issues of resettlement and citizenship. It concludes that this halfway house in Iceland is more integrated into penal practice than halfway houses in Denmark, Norway or Sweden but that the citizenship status of its residents, in particular in relation to various forms of benefits, requires strengthening. Finally, this article hopes to serve as an invitation to study halfway houses elsewhere.